Endogenous bleaching related to external root resorption: a literature review (Research, Society and Development, 2022)
Dental whitening is a satisfactory alternative to devitalized teeth that present chromatic changes, however the association between intracoronary whitening and external cervical resorption is a debatable issue, since tooth whitening possibly causes external root resorption. The etiology of bleaching-related external cervical resorption is not known; however, it is believed that the bleaching gel extravasates beyond the root apex, initiating an inflammatory response that results in the loss of dental tissue. Objectives: Address tooth whitening and the causes of external root resorption, highlighting the interventions that can be performed. Methodology: It consists of a literature review in the following databases: Bireme (Regional Library of Medicine), PubMed/medline (United States National Library of Medicine, Latin American and Caribbean Literature in Health Sciences (LILACS). Keywords “Internal Dental Whitening”, “External Cervical Resorption”, “Aesthetics.” Literature Review: Tooth whitening is recommended for being a conservative and aesthetic technique in the treatment of darkened non-vital teeth. internal, raises questions for compromising the prognosis of whitening. Cervical resorption can come from several causes, it is important to verify the individual predisposition, history of trauma to the tooth, presence of secondary contamination by bacteria or infiltration by the bleaching agent. prevention and the whitening process are essential for a good long-term result. Conclusion: There are several causes for tooth darkening, and internal tooth whitening is a much-requested therapy in this regard, in view of this, the recommendation of safer procedures is essential to avoid an inflammatory response in the periodontium and a possibility of external root resorption.